THE EFFECT OF PERCEIVED AUTHENTIC LEADERSHIP ON EMPLOYEE ENGAGEMENT - Sharifah Noraida Syed Zainal Abidin (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The study examines the effect of perceived authentic leadership on employee engagement. This cross-sectional study accumulated the data through a structured questionnaire survey from a purposive sample of 260 full-time employees from selected Malaysian small and medium budget hotels located in Kuala Lumpur and Selangor. The data were analyzed using stepwise multiple regression analyses. The results showed that from four components of authentic leadership, self-awareness and balanced processing behaviors of owner-managers contribute to physical, emotional and cognitive engagement of employees in the workplace. Accordingly, these findings present empirical evidences on leader-employee relationship, particularly in the context of Malaysian small and medium budget hotels. Further, the findings of this study add new knowledge to the existing literature by providing information related to the effect of each authentic leadership component on employee engagement. The findings also can be a useful guidance for owner-managers on how to encourage employees to be highly engaged in workplace.